Optimisation of the Use of Cultivation System Technology to Increase Tilapia (Oreocromis niloticus) Production in Intensive Cultivation in the Era of Modernisation - Santikawati, Susi; Batubara, Lenni Wahyuni (Jurnal Perikanan dan Kelautan, 2025)
Tilapia (Oreochromis niloticus) is one of the main commodities in freshwater aquaculture because it is highly adaptable and easy to breed. In intensive aquaculture systems, production success is highly dependent on fish growth, which is closely related to feed availability and water quality. This study aims to analyze the effectiveness of modern aquaculture technologies, namely the biofloc system, aquaponics, and the Recirculating Aquaculture System (RAS), in supporting the success of tilapia aquaculture. The research was conducted in August 2025 at the Freshwater Aquaculture Center of the Sibolga College of Fisheries, North Sumatra. The research method used a completely randomised design with four treatments and three replicates. The results showed that the aquaponics technology (P3) produced the highest absolute weight growth (9.97±0.02 g), specific growth rate (4.26±0.00%/day), and absolute length (1.77±0.06 cm), followed by RAS (P2), control (P0), and biofloc (P1). The survival rate across all treatments ranged from 95.33% to 97.33%, indicating Tilapia's good adaptability to various farming systems. Water quality parameters were within optimal ranges: 29-30°C, pH 6.1-7.6, dissolved oxygen 4.5-5.0 mg/L, and ammonia 0.0001-0.0005 mg/L. The aquaponic system showed the most stable water quality with the lowest ammonia concentration (0.0001-0.0003 mg/L). This study demonstrates that aquaponic technology provides the best treatment for modernised intensive tilapia farming